VGLL2-NCOA2 leverages developmental programs for pediatric sarcomagenesis - Sarah Watson; Collette A. LaVigne; Lin Xu; Didier Surdez; Joanna Cyrta; Delia Calderon; Matthew V. Cannon; Matthew R. Kent; Katherine M. Silvius; Jack P. Kucinski; Emma N. Harrison; Whitney Murchison; et al. (Cell Reports, 2023)
Summary: Clinical sequencing efforts are rapidly identifying sarcoma gene fusions that lack functional validation. An example is the fusion of transcriptional coactivators, VGLL2-NCOA2, found in infantile rhabdomyosarcoma. To delineate VGLL2-NCOA2 tumorigenic mechanisms and identify therapeutic vulnerabilities, we implement a cross-species comparative oncology approach with zebrafish, mouse allograft, and patient samples. We find that VGLL2-NCOA2 is sufficient to generate mesenchymal tumors that display features of immature skeletal muscle and recapitulate the human disease. A subset of VGLL2-NCOA2 zebrafish tumors transcriptionally cluster with embryonic somitogenesis and identify VGLL2-NCOA2 developmental programs, including a RAS family GTPase, ARF6. In VGLL2-NCOA2 zebrafish, mouse, and patient tumors, ARF6 is highly expressed. ARF6 knockout suppresses VGLL2-NCOA2 oncogenic activity in cell culture, and, more broadly, ARF6 is overexpressed in adult and pediatric sarcomas. Our data indicate that VGLL2-NCOA2 is an oncogene that leverages developmental programs for tumorigenesis and that reactivation or persistence of ARF6 could represent a therapeutic opportunity.